Learning English And Arabic In Wates Hamlet, Beringin Village, Ngaliyan District, Semarang City - Anisa Al Furochmatin Anisa; Dhea Aulia Damayanti Dhea (CONSEN: Indonesian Journal of Community Services and Engagement, 2021)
Language is an important communication tool. Where humans can convey thoughts, feelings and all what they want and want to say. The development of the times is getting more advanced, changes are increasingly progressive and increasing. We the successors of the nation, are increasingly demanded for the progress of the Indonesian state.In the past we were only obliged to speak Indoneasian, in contrast to now we have to be able to speak international languages.The goal is the compete for the advancement of this country. These foreign languages are mainly English and Arabic, both of which are the most famous and oldest international languages the world. The whole world knows the language. Whether it is English, Japanes, Arabic, European, American including Indonesia. Especially now,the world is being shaken by the Covid 19 outbreak. As a result, educational institutions that should function normally switch from offline to online. This is causes many problems, one of which is mastery of foreign languages. Online learning makes results that are not optimal.Here KKN RDR 75 Conducts English and Arabic foreign language learning activitieswith TPQ Baitul Istiqomah children for grades 4-6. We help them to better master the basics of this foreign language. We feel this activity is very useful and the results are no less great.